POTRET KELAM MODERASI BERAGAMA: KONDISI PENDIDIKAN PENGHAYAT KEPERCAYAAN DI JAWA TENGAH TAHUN 2020-2021 - Haryono, Satrio Dwi (UIN Raden Mas Said Surakarta, 2023)
Today, religious moderation is the mainstream in building tolerance among religious communities. Various dimensions of life are deemed necessary to internalize the values of religious moderation. Education is one of the various dimensions of life targeted by Religious Moderation. The issue of religion and the flow of adherents is also an interesting study in Religious Moderation. This is because adherents are also recognized as citizens who have the same rights as adherents of other religions. In this article, we will explain how Religious Moderation responds to the flow of adherents in the educational dimension. Using a qualitative research model through library research that relies on the Semarang Social and Religious Studies Institute's Annual Report Book for 2020 and 2021. The data analysis technique in this article uses the induction method. By referring to specific facts that eliminate the basic assumptions of a theory. The results of the research presented in this article state that there is still a lot of discrimination experienced by adherents in the educational dimension. Even though there are regulations that regulate this. Also, the Religious Moderation movement wants to create an inclusive and tolerant society but still, the results are not optimal.